Psicodrama e seu dionisismo : percursos de uma clínica desviante - Melo, Aldo Rezende de (2015)
The aim of this study is to analyse the trajectory of cuts production practices and knowledge in Psychodrama, regarding the diversion of certain clinical traditions and conservative dramaturgies of the early twentieth century, through the invention of the concept of creaturgie. Thus, it analyzes the assertion of the political strength of the Theatre of Spontaneity and Psychodrama, both created by Jacob Levy Moreno, highlighting their practices in the exercise of a Dionysian ethos, questioning and disruptive. We pursue, from the analysis and theoretical stitching, inside of Psychodrama and theatrical and philosophical intercessors, trails that give lanes in addition to the cultural psychodrama preserves, in order to destabilize concepts and practices already grounded, crystallized and put this knowledge at the surface of life. Fertile hybrids, besides the interface between art and clinic, necessary for continued significant reinvention of the ways to care for and to practice the Theatre of Spontaneity. We see the possibility of alliances with theoretical authors of different theoretical productions, but they thought the clinical and theater in their deviant functions. Then we use the argument of Jacques Rancière on the " Emancipação do Espectador" ; the Deleuzian concept of " intercessors " and his notion of "minor theater " to put the psychodrama and theatrical thought moving; and Artaudian concept of " body without organs " operated by Deleuze , analyzing and questioning psychodramatic concepts in their aesthetic , political and ethical treatment